Study on ventilated cavity uncertainty of the vehicle under stochastic conditions based on the Monte Carlo method. (1st November 2021) - Sun, Longquan; Li, Wenpeng; Ma, Guihui; Chen, Yingyu; Fang, Ming; Zhang, Wangkai; Yao, Xiongliang
Abstract: Ventilated cavities play an important role during water-exit of underwater vehicles. However, the development of ventilated cavities suffers various uncertainties, which lead to remarkable uncertainty in the cavity shape and internal fluid field structure. By constructing the stochastic sample space based on the Monte Carlo method, this paper investigates the uncertainty of the ventilated cavity under stochastic conditions (incoming flow velocity, ventilation flow rate, and ambient pressure). The results show that the covering area of the ventilated cavity can provide good pressure-equalizing robustness under stochastic conditions. The cavity length and re-entrant pressure at the cavity tail are sensitive to stochastic conditions. The vortex structure inside the cavity expands with the development of the re-entrant jet and gradually transforms from multiple pairs of vortices to a single large-scale vortex. The high standard deviation of the phase volume fraction also transforms from the middle of the vortex pair to the tail of the large-scale vortex. The structure and strength of the vortex in the air phase region are not sensitive to stochastic conditions, but the re-entrant jet at the cavity tail is more sensitive to stochastic conditions, which lead to an increase in the standard deviation of pressure at the cavity tail. Highlights: The covering area of ventilated cavity has good pressure-equalizing robustness. . The cavity length and re-entrant pressure are sensitive to stochastic conditions. . The inside pressure of ventilated cavity is not sensitive to stochastic conditions. .